Nail lacquer films' surface energies and in vitro water-resistance and adhesion do not predict their in vivo residence - Sudaxshina Murdan; Amani Bari; Suleman Ahmed; Basma Hossin; Laxmi Kerai (University of Huddersfield Press, 2017)
The in vivo residence of nail lacquers (which are ideal topical drug carriers for the treatment of nail diseases) determines their frequency of application, and is thereby expected to influence patient adherence and success of treatment. Thus in vitro measurements to indicate lacquers' in vivo residence are routinely conducted during formulation development. However the literature on in vitro-in vivo correlations is severely limited. Thus, the aim of the work discussed in this paper was to investigate correlations between in vivo residence and in vitro film resistance to water, in vitro film adhesion and surface energy of lacquer films. In vivo measurements were conducted on fingernails in six volunteers. Seven commercially available nail lacquers were tested in commonly-used measurements. Correlations between in vivo residence and in vitro water resistance and adhesion were found to be extremely poor. The surface energies of the lacquer films (which were between 33 and 39 mJ/m2) were also not predictive of in vivo residence. High density polyethylene (HDPE) sheet - whose surface energy was determined to be similar to that of the human nailplate - was found to be a suitable model for the nailplate (when investigating surface energy) and was used in a number of experiments.